Effect of kinesio taping intervention on the muscle strength and balance of college basketball players with functional ankle instability - Li, R.; Qin, R.; Tan, Y.; Liu, H.; Wang, K.; Cheng, L. (Frontiers in Physiology, 2023)
Objective: The aim of this study was to investigate the effects of acute Kinesio Taping (KT) intervention on the muscle strength and balance ability of college basketball players with functional ankle instability (FAI).